Five in he Bed - Ladybird Books (UK Ladybird, 2012)
This sturdy sing-along rhyme book from Ladybird is perfect for sharing with young children. There's a different verse from the well-loved counting rhyme 'Five in the Bed' to sing along to on each page, plus fun peek-through holes throughout
Rhymes and Songs
Keywords: English poetry